IMPLIKASI PERNIKAHAN DINI TERHADAP HAK-HAK KEWARGANEGARAAN DAN DAMPAK PSIKOLOGIS PADA PASANGAN MUDA STUDI KASUS DESA PEKALOBEAN KABUPATEN ENREKANG - Wulandari; Ahmad Kamil; Dedi Setiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Implications of early marriage on citizenship rights and psychological impacts on young couples in early marriage in Pekalobean Village. Through a qualitative approach, this study found that early marriage has a significant impact on the fulfillment of citizenship rights, including the right to education, the right to work, the right to health services, and the right to legal protection. Young couples who marry at an early age often lose access to education, have difficulty getting decent work, face limited health services, and have a poor understanding of their legal rights. In addition, this study also identified the psychological impacts experienced by couples in early marriage, such as mental stress due to the burden of responsibility, feelings of loneliness and social isolation, conflict and tension in the household, and mental health risks. However, some young couples managed to develop strategies for dealing with psychological problems, such as seeking support from parents, improving communication with their partners, and participating in Posyandu programs or village activities. The positive impacts felt include independence and a sense of responsibility that grows along with the challenges faced. Based on these findings, this study recommends the need for holistic intervention from the government, non-governmental organizations, and community leaders to improve access to education, health services, and psychological support for couples in early marriage. In addition, early marriage prevention programs through education and community empowerment need to be improved to reduce the negative impacts and maximize the positive potential of early marriage.